2009
DOI: 10.1158/1078-0432.ccr-08-1931
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of a Topoisomerase I Inhibitor, Karenitecin, by the Histone Deacetylase Inhibitor Valproic Acid in Melanoma: Translational and Phase I/II Clinical Trial

Abstract: Purpose: The novel topoisomerase I inhibitor karenitecin (KTN) shows activity against melanoma.We examined whether histone deacetylase inhibition could potentiate the DNA strand cleavage, cytotoxicity as well as the clinical toxicity, and efficacy of KTN in melanoma. Experimental Design: Apoptosis, COMET, and xenograft experiments were carried out as described previously. A phase I/II trial of valproic acid (VPA) and KTN was conducted in patients with stage IV melanoma, with any number of prior therapies, East… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 25 publications
0
60
0
2
Order By: Relevance
“…A similar result was obtained in cultures simultaneously stimulated with 1 mM VPA and 0.5 M etoposide; therefore, VPA made M14 cells more sensitive to standard chemotherapy. This suggests that some of the HDACis may be useful in the combined therapy of malignant melanoma [42]. It is noteworthy that the results presented in Fig.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A similar result was obtained in cultures simultaneously stimulated with 1 mM VPA and 0.5 M etoposide; therefore, VPA made M14 cells more sensitive to standard chemotherapy. This suggests that some of the HDACis may be useful in the combined therapy of malignant melanoma [42]. It is noteworthy that the results presented in Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Many HDACis, among them VPA, are currently undergoing phase I or II clinical trials [11,41]. Daud et al [42] used VPA (30-90 mg/kg/24 h) and the topoisomerase I inhibitor Karenitecin (KNT at 0.8 and 1 mg/m 2 /24 h) and achieved stabilization of the disease in 13 out of 33 (39%) patients with the diagnosed melanoma. The phase I and II clinical trials conducted by Rocca et al [11] revealed that combined treatment with VPA, decarbazine and INF-γ did not give desirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…VPA pretreatment has been shown to increase the cytotoxicity of the topoisomerase inhibitor karenitecin in melanoma cells and in animal xenografts (53). The VPA-karenitecin combination was clinically evaluated in patients with stage IV melanoma with encouraging results: 47% of the patients had stable disease with median progression-free survival of 10.3 weeks versus 34% with stable disease with median progression-free survival of 7.9 weeks in patients treated with single-agent karenitecin (53).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…VPA possesses a high oral bioavailability and is well tolerated by patients. VPA at up to 75 to 120 mg/kg/day was well tolerated (Mü nster et al, 2007(Mü nster et al, , 2009Daud et al, 2009) …”
Section: Valproic Acidmentioning
confidence: 97%